+0  
 
+1
184
2
avatar+30 

answer to a: Ygs =Ae^-2x + Be^-3x +3x^2 -4x 

im not sure how to do b please help thanks

 Oct 1, 2019
 #1
avatar+6179 
+3

\(y = A e^{-2x}+Be^{-3x} + 3x^2 - 4x\\ \dfrac{dy}{dx} = -2A e^{-2x} -3Be^{-3x} + 6x-4\\ \left . \dfrac{dy}{dx}\right|_{x=0} = -2A -3B - 4 = 7\\ y(0) = A + B = 4\\ -2A -3B = 11\\ A+B = 4\\ \text{I leave you to solve for $A,~B$}\)

.
 Oct 1, 2019
edited by Rom  Oct 1, 2019
 #2
avatar+30 
0

thank you rom.

Staunch  Oct 2, 2019

27 Online Users

avatar
avatar